DOI: 10.11606/t.47.2011.tde-02052011-141852
|View full text |Cite
|
Sign up to set email alerts
|

Habilidades comunicativas e a rede social de apoio de idosos institucionalizados

Abstract: Agradeço a Deus por ter me amparado e concedido força, luz, perseverança e coragem para passar por todas as etapas necessárias no processo de Doutoramento. Agradeço, de modo especial, ao meu prezado Professor orientador Dr. Ailton Amélio da Silva pela competência técnica e humana com que orientou este e outros trabalhos ao longo do processo de Mestrado e Doutorado. Poucas pessoas são tão especiais e gentis na arte de ensinar e orientar. Aos Professores Dr. Klaus Bruno Tiedemann e Dra Mariângela Gentil Savoia p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
3
0
3

Publication Types

Select...
3
2

Relationship

1
4

Authors

Journals

citations
Cited by 6 publications
(6 citation statements)
references
References 41 publications
0
3
0
3
Order By: Relevance
“…For Rosa et al (2007) and Rodrigues (2010), the variable Feel Respected (FR) represents the person feeling loved, wanted and valued, through the establishment of exchange of experiences and conversations that generate affection. It is believed that the establishment of exchanges among participants with members of their network, also associated with the sense of capacity for integration into the digital world, made the elderly feel respected and socially valued.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…For Rosa et al (2007) and Rodrigues (2010), the variable Feel Respected (FR) represents the person feeling loved, wanted and valued, through the establishment of exchange of experiences and conversations that generate affection. It is believed that the establishment of exchanges among participants with members of their network, also associated with the sense of capacity for integration into the digital world, made the elderly feel respected and socially valued.…”
Section: Discussionmentioning
confidence: 99%
“…According to Paula-Couto et al (2008), the relationships of the first circle are identified as being stable, strong and not depending on exercised social roles for their maintenance, being the main sources of support. The members of the first circle and the study participants had already established exchanges support before the use of Facebook, having more intimate relationships, which according to Rodrigues (2010) and Paula-Couto et al (2008) serve as protection in the occurrence of negative events, contributing to increase the subjective well-being of the elderly.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Neste sentido, o apoio social recebido contribui decisivamente para o bem-estar e qualidade de vida do idoso. 21,11 A manutenção de relações sociais com cônjuge, familiares e amigos da mesma geração favorece o bem-estar psicológico e social dos idosos. As mulheres, por serem mais calorosas e capazes de estabelecer relações de intimidade, apresentam redes de relações sociais mais desenvolvidas.…”
Section: As Redes De Apoio Social De Idososunclassified
“…9,10 A institucionalização de idosos ocorre em função de vários motivos, dentre eles, pela diminuição da rede de apoio social. 11 O afastamento dos filhos para constituírem suas famílias, a morte de parentes e amigos e outros fatores fazem com que, gradativamente, a rede social dos idosos diminua, tornando-os mais vulneráveis ao desamparo. Ademais, com a institucionalização e o afastamento dos poucos amigos e membros familiares, a rede de apoio do idoso torna-se ainda mais fragilizada e escassa.…”
Section: Introductionunclassified